What is the relationship between knowledge in mathematics and knowledge in economics? - Jeschke, Colin; Kuhn, Christiane; Lindmeier, Anke; Zlatkin-Troitschanskaia, Olga; Saas, Hannes; Heinze, Aiso (Zeitschrift für Pädagogik, 2019)
Content knowledge (CK) and pedagogical content knowledge (PCK) are considered key aspects of teacher competence. Although teacher education and training programs across disciplines focus on the development of CK and PCK, there is little evidence of whether teachers trained in two subjects benefit from reciprocal effects between knowledge in these subjects. To approach this question, we investigated the correlation between the CK and PCK in mathematics and economics of N = 96 pre- and in-service teachers trained in both subjects. We found a substantial correlation between CK and PCK within a subject and between corresponding knowledge components across subjects, with CK in mathematics related also to PCK in economics. We found that although teachers' professional knowledge structure mirrored domains, CK in mathematics could be useful for teaching economics.
CRIS-Team Scopus Importer:2024-10-02
Keywords: Content Knowledge; Economics; Mathematics; Pedagogical Content Knowledge; Teacher Education; Teacher Knowledge